Empowering Farmers with Integrated Pest Management (IPM) through Effective Technology Communication - Bhushan, K. B.; Goswami, Amit Kumar; Naryal, Avilekh (Research Advances and Challenges in Agricultural Sciences Vol. 8, 2024)
Integrated Pest Management (IPM) is acknowledged as a comprehensive approach to agricultural pest management, aiming to reduce pest populations while considering environmental sustainability. Despite its recognized importance, the practical implementation of IPM remains challenging, particularly in developing countries. This paper reviews the literature on IPM adoption, communication strategies, and challenges encountered in its dissemination. It discusses the information needs of farmers regarding IPM, highlighting the multifaceted strategies required for successful adoption. The role of communication, particularly through avenues such as mass media and Farmers Field Schools (FFS), is explored in facilitating IPM dissemination. Challenges in IPM adoption, including knowledge gaps, outreach limitations, socio-economic factors, institutional barriers, and others, are identified and categorized. The paper emphasizes the necessity for effective science and technology (S&T) communication to bridge the gap between stakeholders' understanding and the complexities of IPM. This review underscores the importance of tailored communication approaches in promoting IPM adoption and addressing the challenges hindering its widespread implementation.